Implementation of on-line clutch pressure estimation for stepped automatic transmissions - Sarawoot Watechagit (2018)
On-line estimation of clutch pressures in hydraulically powered stepped automatic transmissions can be useful for on-line diagnostics or development of closed-loop transmission control to improve shift quality. This paper presents the development and implementation of a model-based sliding mode observer to provide on-line estimates of clutch pressures for the clutches involved in gear shifts. The estimation of transmission input torque (torque converter turbine torque), which is needed by the observer for accurate clutch pressure estimation but is not available, is also addressed here and implemented using an adaptive sliding mode observer. The resulting observers are validated via off-line simulation tests, as well as on-line tests at different sampling frequencies on a test vehicle, in order to demonstrate observer performance and establish the feasibility of the approach. ©2005 AACC.